CHARACTERIZATION AND ANTIOXIDANT ACTIVITY OF CASHEW NUT BRAN IN DIFFERENT STAGES OF PROCESSING - SOARES, DENISE JOSINO; SILVA CÂMARA, CRISTIANE RODRIGUES; DE FIGUEIREDO, EVÂNIA ALTINA TEIXEIRA; MAIA, GERALDO ARRAES; DE SOUSA, PAULO HENRIQUE MACHADO; DE FIGUEIREDO, RAIMUNDO WILANE (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2012)
The present work aimed to characterize the cashew nut bran during several stages of processing, with emphasis in the quantification of total extractable polyphenols and total antioxidant activity. The cashew nut bran was analyzed for the following parameters: water activity, total acidity, pH, moisture, ash, lipids, proteins, carbohydrates, total extractable polyphenols and total antioxidant activity by the methods ABTS•+ and DPPH•. There was a decrease in the water activity and moisture in cashew nut bran during processing. The highest values of total extractable polyphenols and antioxidant activity were observed in raw bran due to peel adhered in these nuts.